AKSINA Education with Crossword Puzzle on Knowledge of Earthquake Disaster Preparedness in Elementary School Students - Km Indah Kusuma Dewi, Ni; G. A. Ari Rasdini, I.; Pt. Gd. Putra Yasa, I Dw.; Made Wedri, Ni (Nursing and Health Sciences Journal (NHSJ), 2024)
Based on data from the Badan Nasional Penanggulangan Bencana (BNPB) in 2016, out of the 2000 biggest disasters including earthquakes that occurred in Indonesia, the most victims were children. Disaster preparedness education can be carried out early on in schools so that children know how to avoid and save themselves from disasters. This study aims to determine the effect of education "AKSINA" with crosswords on knowledge of earthquake preparedness disaster in elementary school students. The data collection method uses an earthquake disaster preparedness questionnaire sheet. All data were normally distributed and analyzed using paired t-test statistics. There is a significant effect of providing education "AKSINA" with crosswords puzzle as media on earthquake preparedness for students in grades IV and V with a p-value = 0.000<alpha (0.05). The results of this study indicate that education with crossword puzzle games has proven effective in increasing students' preparedness knowledge for earthquake disasters. This research is expected to be a reference in providing disaster preparedness education with various game media to increase student knowledge.